2020
DOI: 10.1051/0004-6361/202037642
|View full text |Cite
|
Sign up to set email alerts
|

Cold molecular gas and PAH emission in the nuclear and circumnuclear regions of Seyfert galaxies

Abstract: We investigate the relation between the detection of the 11.3 μm polycyclic aromatic hydrocarbon (PAH) feature in the nuclear (∼24−230 pc) regions of 22 nearby Seyfert galaxies and the properties of the cold molecular gas. For the former we use ground-based (0.3−0.6″ resolution) mid-infrared (mid-IR) spectroscopy. The cold molecular gas is traced by ALMA and NOEMA high (0.2−1.1″) angular resolution observations of the CO(2–1) transition. Galaxies with a nuclear detection of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 110 publications
4
12
0
Order By: Relevance
“…The nuclear molecular gas surface density is very high: Σ H 2 = 10 4.4 M pc −2 . It is comparable to the Σ H 2 observed in more extreme ULIRGs (e.g., Wilson et al 2019), about 200 times higher than the values observed in nearby disk galaxies (e.g., Bigiel et al 2011), and ∼10 times higher than in local Seyfert galaxies (e.g., Alonso-Herrero et al 2020). Therefore, this object allows us to carry out a detailed study of the properties of outflows produced in compact and obscured nuclear regions similar to those of more distant starburst-dominated ULIRGs.…”
Section: Introductionsupporting
confidence: 66%
“…The nuclear molecular gas surface density is very high: Σ H 2 = 10 4.4 M pc −2 . It is comparable to the Σ H 2 observed in more extreme ULIRGs (e.g., Wilson et al 2019), about 200 times higher than the values observed in nearby disk galaxies (e.g., Bigiel et al 2011), and ∼10 times higher than in local Seyfert galaxies (e.g., Alonso-Herrero et al 2020). Therefore, this object allows us to carry out a detailed study of the properties of outflows produced in compact and obscured nuclear regions similar to those of more distant starburst-dominated ULIRGs.…”
Section: Introductionsupporting
confidence: 66%
“…This is in agreement with experimental (Monfredini et al 2019; Quitián‐Lara et al 2018) and observational works (Lambrides et al 2019; Minsley et al 2020). This is also consistent with Alonso‐Herrero et al (2020), who points out that PAH molecules are being shielded from AGN radiation by the large content of molecular cold gas.…”
Section: Resultssupporting
confidence: 91%
“…Concerning the strength of the AGN, we find that AGNdominated systems are generally located in the leftmost corner of the grid or even outside of the range of the grid (with measured 6.2/7.7 PAH ratios smaller than 0.25; see Fig. 11 and also Alonso-Herrero et al 2020). The fact that a fraction of AGN-dominated systems lies beyond the values predicted by the current grid suggests that perhaps larger PAH molecules (N c >400), are required to reproduce their PAH ratio values.…”
Section: Pah Diagnostic Diagramsmentioning
confidence: 79%
“…We note that the Spitzer/IRS spectra of the majority of the galaxies in this sample have been previously studied (e.g. Baum et al 2010;Gallimore et al 2010;LaMassa et al 2010;Lyu & Rieke 2018;Alonso-Herrero et al 2020) by using the same method to extract the PAH feature strengths.…”
Section: Mir Modellingmentioning
confidence: 99%
See 1 more Smart Citation